2011
DOI: 10.1162/jocn.2010.21479
|View full text |Cite
|
Sign up to set email alerts
|

Medial Prefrontal Cortex Predicts Intertemporal Choice

Abstract: Abstract■ People often make shortsighted decisions to receive small benefits in the present rather than large benefits in the future, that is, to favor their current selves over their future selves. In two studies using fMRI, we demonstrated that people make such decisions in part because they fail to engage in the same degree of self-referential processing when thinking about their future selves. When participants predicted how much they would enjoy an event in the future, they showed less activity in brain r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
84
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(97 citation statements)
references
References 59 publications
6
84
0
2
Order By: Relevance
“…What this suggests is that when self-relevant episodes are simulated from a thirdperson vantage point (e.g., distant-future events), the imagined version of the self may be stripped of the experiential components that produce the corporeal feeling of personal identity, hence blurring the boundary between the self and others (Hershfield, 2011;Mitchell, Schirmer, Ames, & Gilbert, 2011;Pronin & Ross, 2006). In this way, shifts in vantage point have important implications for the temporal continuity of self.…”
Section: Discussionmentioning
confidence: 99%
“…What this suggests is that when self-relevant episodes are simulated from a thirdperson vantage point (e.g., distant-future events), the imagined version of the self may be stripped of the experiential components that produce the corporeal feeling of personal identity, hence blurring the boundary between the self and others (Hershfield, 2011;Mitchell, Schirmer, Ames, & Gilbert, 2011;Pronin & Ross, 2006). In this way, shifts in vantage point have important implications for the temporal continuity of self.…”
Section: Discussionmentioning
confidence: 99%
“…Hariri et al (2006) have shown that higher discounters exhibit a greater VS response to unpredicted rewards. Others have shown that higher discounters exhibit a greater difference in BOLD activity between judgments of oneself in the present compared with the future (Ersner-Hershfield et al, 2009;Mitchell et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Bartels and Rips (2010) found that changes in perceived connectedness across time mirror changes in patience over time. Ersner-Hershfield et al (2009a) and Mitchell et al (2010) showed that neural correlates of connectedness correlate with discounting.…”
Section: Diachronic Identity and The Persistence Of Individual Personsmentioning
confidence: 99%